Frequency and Control of Subsurface Preferential Flow: From Pedon to Catchment Scales. Issue 2 (13th March 2015) - Liu, Hu; Lin, Henry
Abstract : Quantitative assessment of frequency and control of preferential flow (PF) across the landscape has been largely lacking. Previous work evaluated PF occurrence at 10 sites along a hillslope in the Shale Hills Catchment using soil moisture response to 175 precipitation events. We expanded the analysis to include (i) 237 additional events to test the temporal consistency and predictability of PF occurrence and (ii) 25 additional sites to upscale to the entire catchment. The results showed considerable temporal consistence in both frequency and main controls of PF at the hillslope scale, attributed largely to statistical stability of precipitation patterns during the 6.5‐yr monitoring and relatively stable subsurface PF paths. Generally, PF tended to occur more often in response to intense rainfalls and favored conditions at dry hilltop or wet valley sites. When upscaling to the catchment, topographic controls became more evident, leading to the identification of a hidden subsurface PF network. Higher frequency of PF occurred at the hilltop (average 46%) and the valley floor (average 41%), while the overall average frequency for swales was 26% and that for planar and convex hillslopes was 18%. Soil‐terrain attributes provided a limited estimation ( R 2 = 0.43–0.48) of PF occurrence, suggesting complexities involved in PF dynamics. This study confirmed that the initiation and persistence of PF were controlled by interactions among landforms, soils, initial moisture conditions, precipitation, and seasons. Further investigations of these key controls can lead to improved understanding and modeling of PF from pedon to catchment scales.